History of Organization of Administration in Western Territory in 30-40-ies of XlX-th Century - O. V. Lepesch (Наука и техника)
Main purpose of the paper is to study one of territorial committees of the second quarter of the XIX-th century that is the Committee of Western Provinces. The Russian government established this Committee with the purpose to arrange administration of the Western territory after the rebellion in 1830-1831. High state officials and representatives of local authorities (governors and governorgenerals) were members of the Committee. The Committee of Western Provinces was busy with the solution of problems concerning full integration of the Western territory with the Russian Empire.